(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The intellect and the speech, faculties commonly used to distinguish humans from other living beings, represent instead the point of contact between man and machine. The vocal assistant combines these qualities and makes use of them to gain a pivotal role in the healthcare system. This scenario has great potential, but shows strong issues too in terms of compliance with the General Data Protection Regulation. The aim of the paper is twofold. Firstly, to critically discuss the implications and the effectiveness of the safeguards provided by Article 22 of the GDPR in case of automated decision making in the healthcare field. Secondly, to analyze the organizational and technical security measures to be enforced, stressing the importance of the data protection by design approach. Further, it will emerge the need for the close collaboration of several professionals and knowledges to solve the riddle.